Internalization of Wudu Practice as a Strategy for Clean and Healthy Living Behavior: An Integrative Pedagogical and Medical Analysis: Internalisasi Praktik Wudhu sebagai Strategi Pendidikan Hidup Bersih dan Sehat (PHBS): Analisis Integratif Pedagogis dan Medis - Suryatna, Yayat; Kosim, Kosim (jsd: Journal of Society and Development, 2025)
Early inculcation of Clean and Healthy Living Behavior (PHBS) is a primary pillar of public health; however, Wudhu (ablution) is often viewed merely as a spiritual ritual, overlooking its substantial hygiene benefits. This study aims to analyze the role of wudu as a systematic health education instrument. The method used is descriptive qualitative with a library research approach, integrating fiqh literature, educational theory, and clinical medical evidence. The results indicate that wudu meets clinical personal hygiene standards through a mechanism of habitualization. Medically, wudu stages are proven effective for pathogen decontamination; hand washing disrupts the fecal-oral transmission of Escherichia coli and Salmonella bacteria, while istinsyaq functions as nasal irrigation that reduces Staphylococcus aureus colonization and enhances mucociliary clearance in the nasopharynx. In conclusion, reconstructing the understanding of wudu from a mere ritual into a preventative sanitation procedure can accelerate the internalization of PHBS values in educational and community settings.